Post contract final account / Mohamad Syafiq Asyraf Mohamad Shokri - Mohamad Shokri, Mohamad Syafiq Asyraf (Universiti Teknologi MARA, Perak, 2014)
This report briefly explains the final account process. It is produced from five months’ experience in the construction project. This report is divided into three sections starting with the background of the company as well as the background of the construction project. The title of this report is final accounts that are related in post contract. This report gives more experience and knowledge about the final account process. Construction projects generally comprise four stages, namely, design/planning stage, tender stage, construction stage and final account/defect liability stage. Whilst many research studies addressed construction projects performance by examining critical factors to the project success or failure, most of them are focused on construction stage with little attention to final account stage. In fact, the backlogs in settlement of Final Account have existed for decades and the important factors significantly affecting settlement of Final Account of construction projects are, among other things, largely founded as project-related, Contractor-related and Engineer-related. These factors usually attract less attention and priority from project participants and contracting parties in the less pressing final account stages. Undue protracted inaction makes settlement of Final Account more difficult and frequently gives rise to unnecessary dispute.